Association Between Estimated Pharmacokinetic/Pharmacodynamic Predictions of Efficacy and Observed Clinical Outcomes in Obese and Nonobese Patients With Enterobacteriaceae Bloodstream Infections - Santibañez, Melissa (Open Forum Infect Dis, 2019)
BACKGROUND: Evidence on pharmacokinetic/pharmacodynamic (PK/PD) alterations and clinical outcomes in obese patients with serious infections remains limited. This study aimed to evaluate predicted PK/PD indices of efficacy and observed clinical outcomes between obese and nonobese patients receiving cefepime or piperacillin-tazobactam for Enterobacteriaceae bacteremia. METHODS: This was a retrospective study of adult inpatients from 1/2012 to 9/2015 with Enterobacteriaceae bacteremia who received empiric cefepime or piperacillin-tazobactam. The primary outcome was clinical cure. First-dose free-drug exposure was estimated via predicted concentrations generated from population PK analyses and used to assess PD target attainment (>50% fT > minimum inhibitory concentration [MIC]) for the specific Enterobacteriaceae isolate. Multivariable logistic regression was utilized to identify independent predictors of clinical cure. RESULTS: One hundred forty-two patients were included, 57 obese and 85 nonobese. Clinical cure was achieved in 68.4% of obese and 62.4% of nonobese patients (P = .458). No significant difference in outcomes was observed when evaluated by World Health Organization (WHO) obesity classes. The PK/PD target was achieved in 98.2% of obese and 91.8% of nonobese patients (P = .144). Independent predictors of clinical cure were immunosuppression and a shorter duration of bacteremia. Obesity was not identified as a significant predictor of clinical outcomes. CONCLUSIONS: Neither predicted PK/PD parameters nor clinical outcomes differed significantly between obese and nonobese patients treated with piperacillin-tazobactam or cefepime. As the majority of patients received extended-infusion piperacillin-tazobactam for bacteremia due to pathogens with low MICs, the potentially detrimental pathophysiologic derangements caused by obesity may not have been realized. Further studies are warranted to establish the optimal treatment of serious infections in obese patients.